2021
DOI: 10.3390/ijms221910541
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive NAFLD Signature in Adipose Tissue from Women with Severe Obesity

Abstract: Development and severity of nonalcoholic fatty liver disease (NAFLD) have been linked to obesity and white adipose tissue (WAT) dysfunction plays a key role in this relation. We compared the main features of subcutaneous (SAT) and visceral WAT (VAT) tissue dysfunction in 48 obese women without (Ob) and with NAFLD (Ob-NAFLD) undergoing bariatric surgery and matched for age, BMI and T2D status. Fat cell area, adipocyte size distribution, the degree of histological fibrosis and the mRNA expression of adipokines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Following functional enrichment analysis, the upregulated DEGs were involved in hormone response, cellular response to fatty acids, regulation of adipocyte differentiation, positive regulation of Akt signaling, and regulation of cell adhesion, which are in line with the previous findings. The disease–gene interactions further revealed several conditions, some of which are known to be associated with obesity, such as heart disease, fatty liver disease [ 16 ], and nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following functional enrichment analysis, the upregulated DEGs were involved in hormone response, cellular response to fatty acids, regulation of adipocyte differentiation, positive regulation of Akt signaling, and regulation of cell adhesion, which are in line with the previous findings. The disease–gene interactions further revealed several conditions, some of which are known to be associated with obesity, such as heart disease, fatty liver disease [ 16 ], and nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that VAT exosomes can induce TGF-β pathway dysregulation in hepatocytes in vitro, indicative of a possible role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD) [ 19 ]. Recently, a distinctive NAFLD-associated transcriptomic signature, which included a highly expressed TGF-β1, has been reported in the white AT of severely obese females [ 16 ]. Besides vascular inflammation, weight gain, kidney failure, and liver and heart diseases, the disease–gene interaction also revealed unipolar depression, various cancers, and scoliosis, all known risks for obese children [ 3 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have suggested that SFRP5 is a protective adipokine with an anti-inflammatory role in NAFLD pathogenesis [ 7 , 20 ]; however, inconclusive results have been reported. In this sense, given that the adipose tissue-liver axis seems to be relevant in the progression of NAFLD [ 16 ], in this study, we evaluated the SFRP5/WNT5A-PPARγ pathway in adipose tissue samples of women with different degrees of NAFLD associated to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In other ways, the expression of SFRP5 in adipose tissue of NAFLD patients it could be also increased by the liver disease itself given the intercommunication between both tissues [ 16 ]. Since obesity has been suggested to induce SFRP5 expression in mice and humans [ 64 ], we hypothesize that NAFLD may result in the same effect by increasing metabolic imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation